Diseño de derivados fitoquímicos contra la alopecia - García de León, Diana Margarita; Magaña Martínez, Juan; Morales García, Roxana; Ramírez Ramírez, Miriam Liliana; Díaz Cervantes, Erik (JÓVENES EN LA CIENCIA, 2021)
Palabras clave: Capsaicina; Alopecia; Docking-molecular.